Proceedings of the 2017 International Conference on Applied Mathematics, Modelling and Statistics Application (AMMSA 2017) 2017
DOI: 10.2991/ammsa-17.2017.13
|View full text |Cite
|
Sign up to set email alerts
|

Stability of a Paddy Ecosystem with Time Delay

Abstract: Abstract-A delay differential equation model of paddy ecosystem was put forward to reveal the interaction among rice, weeds and inorganic fertilizer on the system. The results show that, the system exists a rice and weed extinction equilibrium, and it also exists a rice extinction or weed extinction equilibrium. Their stable and unstable conditions are obtained. Moreover, Hopf bifurcations occur at the rice extinction or weed extinction equilibrium as the delay crosses some critical values. According to the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…As everyone knows, there are a lot of interacting components in a paddy ecosystem, such as weeds, inorganic salts, light intensity, herbivore, especially human activities, which make it become a complex nonlinear system. Recently, some mathematical models of paddy ecosystem have been proposed and some valuable results have been achieved [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As everyone knows, there are a lot of interacting components in a paddy ecosystem, such as weeds, inorganic salts, light intensity, herbivore, especially human activities, which make it become a complex nonlinear system. Recently, some mathematical models of paddy ecosystem have been proposed and some valuable results have been achieved [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to studying the stability of equilibria for fractional order systems, many scholars have also discussed the existence of Hopf bifurcations [13][14][15][16][17]. By extending the integer order paddy ecosystem discussed in [3] to fractional order case, Zhou et al established a fractional order paddy ecosystem with time delay [4]. They obtained the sufficient conditions of the stability of equilibria and the existence of Hopf bifurcation, which are the generalization of the corresponding conditions of integer order systems in [3].…”
Section: Introductionmentioning
confidence: 99%
“…It is a common research method to analyze the interaction of all factors in a population system by using mathematical models [1][2][3][4][5][6][7][8][9][10][11]. As far as we know, there are only a few mathematical models that have been established for paddy ecosystems [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…They also found that the system can exhibit Hopf bifurcation phenomenon and gave the critical value of Hopf bifurcation by taking a system parameter as the bifurcation parameter [13]. Wang et al [12] further studied the interaction of rice, weeds, and inorganic fertilizer in a paddy ecosystem. They discussed the existence and stability of equilibria in a paddy ecosystem.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation